A Comparative Study Between Wireshark and Paessler Router Traffic Grapher (PRTG) in Network Monitoring and Analysis - Anis Nariesha, Alizan; Mohamad Fadli, Zolkipli (INTI International University, 2024)
Network traffic analysis (NTA) plays a major role for monitoring network performance, improving security, and guaranteeing operational efficiency across sectors. This study compares two popular network analysis tools, Wireshark and Paessler Router Traffic Grapher (PRTG), that handle distinct areas of network monitoring. Wireshark focusses on packet-level analysis, making it ideal for comprehensive troubleshooting and security protocol analysis. PRTG, on the other hand, provides a comprehensive picture, monitoring a wide range of network devices and allowing for scalability via distributed monitoring, making it ideal for organizations with complicated infrastructure. This study assesses each tool's capability using essential criteria such as scalability, real-time monitoring, data management, and security features. By understanding the strengths and limitations of Wireshark and PRTG, this paper aims to assist network professionals in choosing the most suitable tool for their specific monitoring and diagnostic requirements. Practical recommendations are provided to guide both beginners and experienced users in leveraging these tools effectively.